Libras as a tool to improve the medical-patient-deaf patient relationship: a brief bibliographic review (Research, Society and Development, 2020)
Objective: To analyze the scientific production on the history of deafness, in Brazil, and the relationship between the doctor and the deaf patient. Method: It is an integrative review, supported by the qualitative method, including manuscripts published in the SciELO, PubMed and BVS databases using the descriptors “Doctor-patient relationship AND Deafness AND Sign Language”, “Doctor-patient relationship AND Deafness”, “ Doctor-patient relationship AND Sign Language ”, in Portuguese and English, in title or abstract. Results: Of the 267 selected articles, preliminarily, only 32 were used for analysis with emphasis on the objectives of the study. Based on the relevant texts, the evolution of the history of deaf education, the emergence of the Brazilian Sign Language (LIBRAS) and its importance for the relationship between the doctor and the patient were analyzed. Final considerations: It was found that there are few articles dealing with the subject matter of the investigation. There is a need for advancement in research that deals with the Brazilian Sign Language as a mechanism capable of improving the relationship between doctor and deaf patients. It is concluded that the relationship between doctor and deaf patient remains a barrier caused by the lack of knowledge of Libras, with the potential to result in wrong diagnoses, breach of medical confidentiality, as well as frustrations on the part of the patient.